THE IMPORTANCE OF THE INTRODUCTION OF SEX EDUCATION IN THE PREVENTION OF SEXUAL ABUSE IN EARLY CHILDHOOD - Arifa Lubis, Sofni Indah (Proceeding International Seminar of Islamic Studies, 2023)
The phenomenon of sexual deviation is starting to be found around us. Therefore the need for prevention and protection of early childhood. One of them starts by providing sex education guidance to children. But there are still many parents who underestimate the importance of sex education being taught from an early age. The purpose of providing sex education is to provide adequate understanding of the process of physical, mental, and emotional maturity and reduce fear and anxiety related to sexual adjustment and development. This study used a qualitative method with a literature study approach. The resulting data analysis is in the form of primary data from a book entitled "Sexuality Education for Children" by Veronika Kusuma, S. Kep., and secondary data from analysis of various journals and supporting documents related to sexual education and the prevention of sexual abuse. The author's reason for taking this book as the basis for primary data is that this book combines three basic sciences at once, namely religion, parenting, and health. Which will be discussed in the discussion in this article. Based on the results of this study, it shows that the importance of introducing sex education is very influential in growing children's characters for the better.